MULTI-ETHNIC SOCIAL CAPITAL AND THE CONDITIONS FOR SUSTAINABLE COMMUNITY INNOVATION IN SEMI-URBAN LAMPUNG - Mulyadi; Hartoyo; Handi Mulyaningsih (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2026)
Community-based initiatives in developing country settings often fail not from a lack of initial participation, but from the absence of the institutional and social conditions needed to sustain what that participation created. The existing literature documents this difficulty consistently: more than seventy percent of such initiatives stagnate or regress within three to five years, particularly when external funding is reduced or removed (Dees et al., 2004; Moulaert et al., 2013). Pasar Yosomulyo Pelangi, known locally as Payungi, a community-run creative market in Kelurahan Yosomulyo, Kota Metro, Lampung, has operated outside this pattern since its founding in October 2018, maintaining viability across economic, social, institutional, and cultural dimensions without recurring external subsidy. This study draws on qualitative fieldwork conducted in Q3 2025 in Kelurahan Yosomulyo, involving in-depth interviews with 23 informants drawn from multiple participant categories, participant observation, and documentary analysis. The analysis reveals three interconnected mechanisms that explain Payungi's durability. First, its institutional design emerged from deliberate learning after an earlier initiative collapsed under administrative boundary conflicts. Second, contrary to the commonly assumed trade-off between bonding and bridging social capital in diverse communities, what the Payungi data shows is that strong bonding capital at the neighborhood level provided the stable foundation from which bridging capital across ethnic, gender, and disability lines could be deliberately constructed. Third, selective formalization, the practice of formalizing legally necessary functions while preserving participatory informality in governance decisions, allowed Payungi to navigate bureaucratic requirements without losing its grassroots character. These findings extend social capital theory for multi-ethnic semi-urban contexts in the Global South and offer practical lessons for community development practitioners.